Pesticide Applicator Update: Choosing Suitable Personal Protective Equipment - Thomas W. Dean (EDIS)
This document describes various articles of personal protective equipment (PPE) that are worn to protect the human body from contact with pesticides or pesticide residues. PPE includes such items as coveralls or protective suits, footwear, gloves, aprons, respirators, eyewear, and headgear. This document is PI-28, one of a series of the Pesticide Information Office, Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published January 2003.